Residential Schools Locations Project
This dataverse contains datasets associated with the Residential Schools Locations Project. This datasets in this project show the precise locations of the Residential Schools (Boarding Schools, Industrial Schools and Hostels) in Nova Scotia, Quebec, Ontario, Manitoba, Saskatchewan, Alberta, British Columbia, Yukon Territory, Northwest Territories and Nunavut. Data was created by Rosa Orlandini with significant contributions from the National Centre for Truth and Reconciliation, and minor contributions from Morgan Hite and Stephanie Pyne.
Keywords: _open access

Historical Atlas of Canada Online Learning Project
Data for maps from the Historical Atlas of Canada Online Learning Project (HACOLP), preserved here largely for preservation purposes. HACOLP was a series of interactive online maps based on maps in the published Historical Atlas of Canada series. Data deposited by Byron Modolfsky, cartographer for the Historical Atlas of Canada, summer 2019.
Keywords: _open access

The Canadian Peoples 1871-1921 census data
The Canadian Peoples (TCP) data infrastructure encompasses 40 million coded and georeferenced census records from 1852-1921 including personal, family and household characteristics for every individual in each enumeration. The Canadian Foundation for Innovation, provincial research funds in Quebec, Ontario and Alberta, nine Canadian universities and Ancestry.com have funded the project. The owner of these data, Ancestry.com, has agreed to license their use for academic research and educational purposes only, with no right to publish, transfer, share, sub-license or distribute any portion of the data. Access to data for research and educational purposes may occur upon approval of a completed application by the TCP approvals committee. Any research institution or research seeking access to any of the data within this collection will need to complete the application form and send it to the TCP project director Kris Inwood at: kinwood@uoguelph.ca The first census year for distribution is 1871; the data for other years will follow as soon as they can be made ready.
Keywords: _open access

Ingenium (Musée des sciences de l’innovation du Canada)
Ingenium – Le Musée des sciences de l’innovation du Canada à Ottawa crée des expositions hors concours, des programmes accessibles et adaptés aux familles ainsi que des recherches collaboratives qui prennent vie grâce à notre collection nationale d’artefacts.
Keywords: _open access

The Montreal star 1951-1979 ([éditeur non identifié])
Keywords: _microfilm

The Montreal daily star 1877-1951 (Graham & Co, proprietors)
Keywords: _BLRCS; _imprimé

Publications – Centre d'histoire et d'archives du travail
Keywords: _imprimé; _microfilm

Archives Deschâtelets-NDC (2023)
Les Archives Deschâtelets-NDC sont les archives historiques et administratives des missionnaires Oblats. Elles ont pour mission d’acquérir, traiter, conserver, améliorer l’accessibilité et diffuser…
Keywords: _imprimé

CUBIQ - Gouvernement du Québec
CUBIQ (catalogue unifié des bibliothèques gouvernementales du Québec) est le catalogue collectif des bibliothèques du RIBG. Il permet de repérer sur Internet les publications disponibles dans les bibliothèques des ministères et organismes du gouvernement du Québec qui utilisent les services du RIBG pour gérer leurs opérations. Sa mise à jour est quotidienne. CUBIQ renferme une collection vaste et diversifiée de : 500 000 livres; 250 000 publications gouvernementales; 14 000 revues et journaux. CUBIQ permet de consulter à l’écran un nombre grandissant de publications. Actuellement, plus de 100 000 titres sont disponibles en ligne.
Keywords: _open access

L'action nationale (BAnQ)
1933-...
Keywords: _open access

La Revue moderne (BAnQ)
1919-1960
Keywords: _open access

La Revue Populaire (Canadiana)
1907-1920
Keywords: _open access

Revue canadienne (Canadiana)
1864-1920
Keywords: _open access

The Canadian magazine (Canadiana)
1893-1921
Keywords: _open access

Canada Census Search - Library and Archives Canada
Application Description
Last Modified: Date modified (YYYY-MM-DD) / Date de modification (AAAA-MM-JJ)
Keywords: _open access

The Black Press
Keywords: _open access

Archives Révolutionnaires
«Projet collectif en activité depuis 2017... intérêt particulier pour les luttes d’émancipation populaires, décoloniales, anti-impérialistes, féministes, LGBTQ+ ou antiracistes dans un horizon communiste et autogestionnaire.»
Keywords: _open access

Affiches de guerre - Calypso
La collection d’affiches de guerre des bibliothèques de l’Université de Montréal se compose de plus de 3000 images produites au cours des deux guerres mondiales ainsi que de l’entre-deux-guerres. Chaque affiche a été numérisée et son contenu a fait l’objet d’une description détaillée.
Keywords: _open access

Canadian War Poster Collection - Rare Books & Special Collections, McGill Library
Keywords: _open access

Artefacts Canada - Gouvernement du Canada, Ministère du Patrimoine canadien
Artefacts Canada propose un accès à de l'information sur des millions d'objets de musées, fournis par des musées et des organismes patrimoniaux de partout au Canada.
Last Modified: 2006-08-24
Keywords: _open access